The Italian morphological concept of rendimento: a parameter for the city’s good form - Ribeiro da Costa, Higor (2019)
How to bring the concept of ‘rendimento’ (yield) to the Portuguese language relating it to the urban scale? Originally developed by Gianfranco Caniggia and his followers of the Italian school of design typology, this concept expresses an idea of efficiency, use and adaptation. It was applied in the interpretation of built structures and territories, but yet not in the analysis and planning of new urban layouts. In this paper, the concept of ‘rendimento’ is interpreted as from its etymology and from the Italian theoretical framework, which is aimed to the study of buildings and territories, and adapted for the urban scale, enabling ‘rendimento’ to be used in new urban designs. Using logical argumentation, the main authors which study this concept and the cities’ formation processes are studied. Thus, their considerations are associated and synthesized in a Portuguese definition. As a result, the concept of ‘urban rendimento’ is developed, translating the relationship between the urban layout and the natural context and topography, which may be used as a parameter for the design of new urban areas. The conclusion points that the ‘rendimento’ concept passes through the relations between ‘collective imaginary’ and landscape, between subject, culture and territory, making possible a more comprehensive understanding of the city and new design approaches.